Eugenika – aspekty historyczne, biologiczne i edukacyjne - Binnebesel, Józef; Baczała , Ditta; Błajet , Piotr (Studia Edukacyjne, 2019)
Eugenics is the selection of desired heritable characteristics in order to improve future generations, typically in reference to humans. The article is about eugenics in historical, biological and educational aspects. The historical aspect is elaborated on and includes early eugenics, eugenics organizations, popular support for eugenics, and anti-eugenics sentiments. Despite the dropping of the term eugenics, eugenic ideas remained prevalent in many issues concerning human reproduction and genetic intervention. “New Eugenics” is a fact. “New Eugenics” includes education. Does it really?